ENSURING THE BEST INTERESTS OF THE CHILD: JUDICIAL CONSIDERATIONS ON POST-DIVORCE CHILD SUPPORT IN LHOKSEUMAWE - Muammar; Faisal; Marlia Sastro; Mukhlis (CV. RADJA PUBLIKA, 2025)
This study examines the existence and effectiveness of the Sharia Court of Lhokseumawe’s rulings on post-divorce child support obligations through a normative-empirical legal research approach. Normatively, the analysis draws on Law No. 1 of 1974 on Marriage, the Compilation of Islamic Law (KHI), and Law No. 35 of 2014 on Child Protection, while empirically it relies on case studies of court decisions and interviews with judges. The findings reveal that the court consistently upholds the father’s responsibility to provide child support after divorce, reflecting alignment with statutory provisions, Islamic principles, and the doctrine of the best interests of the child. However, variations in the determination of support amounts and weak enforcement mechanisms demonstrate a gap between “law in the books” and “law in action.” Sociological analysis further shows that ineffective enforcement disproportionately burdens women and children, exacerbating economic vulnerability and the feminization of poverty. The study concludes that while the normative foundation of child support rulings is strong, their practical effectiveness requires improvements in drafting quality, standardized guidelines, and enforcement mechanisms, alongside greater collaboration between the judiciary, government, and society to ensure substantive justice and child welfare.